Perilaku Seksual Berisiko Pada Remaja di Kabupaten Banyumas - Nina Setiawati; Aprilia Kartikasari; Mekar Dwi Anggraeni; Lutfatul Latifah; Eni Rahmawati (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Background: Risky sexual behavior that is generally carried out by adolescents is an activity that is often carried out when dating, namely holding hands, kissing, and petting and having sex while dating. The increasing percentage of teenagers who have had premarital sex will also increase the negative impacts that can occur, such as teenage pregnancy, sexually transmitted infections, to social impacts in society. Aim:The purpose of this study was to identify risky sexual behavior in adolescents in Banyumas Regency. Methods: This research is a quantitative research with cross sectional research design. The sample of this research is junior high school, high school and vocational school students who attend school in Banyumas Regency. The sampling technique with probability stratified random sampling has been used and obtained 452 respondents. Results: The result show the respondents with risky sexuality were 251 respondents (55.5%). It is known that 231 teenagers with unsafe risky sexual behavior (51.1%) and 20 teenagers with unsafe behavior (4.4%). Most (251 respondents) have held hands with their partners (68.13%), hugged their partners' bodies (49.40%), masturbated (34.66%) and hugged their partners (27.09%). Conclusion: The high percentage of adolescents who have had premarital sexual intercourse will also increase the adverse effects that can occur, such as teenage pregnancy, sexually transmitted infections, to social impacts in society.